(untitled) (Bangladesh Renal Journal, 2026)
Introduction: Multiple myeloma is a common plasma cell malignancy where kidney damage can limit treatment options and lead to poor outcomes. Conventional markers for renal impairment have several limitations whereas NGAL is an early and robust marker of kidney injury and can reflect renal function more accurately than creatinine. Objective: This study aims to explore the relationship between urinary NGAL and treatment response in patients with multiple myeloma with renal involvement. Materials and Method: This prospective observational study was conducted in the Department of Nephrology, BSMMU, Dhaka. A total of 54 diagnosed Multiple myeloma patients were included according to the selection criteria. Baseline Urinary NGAL, Serum β2 microglobulin, S. creatinine levels were measured. Bortezomib based regimen was administered according to NHS guidelines. Follow up was given in the third month of treatment. Data were collected using a predefined data collection sheet. Statistical analyses were performed using software SPSS v-26 Results: The mean age of the participants was 55.7 years. 51.9% of patients were male and 48.1% were female. 77.8 % patients had eGFR value <60 ml/min and Serum â2 microglobulin was raised in 73.2 % patients. The optimal cut-off value for NGAL is 1.54 pg/mL, demonstrating high diagnostic accuracy with a sensitivity of 81.8%, specificity of 81.2%, positive predictive value of 72.0%, and a negative predictive value of 86.2%. Good response was found in 60% and 58.5% in respect to eGFR and S. β2 Microglobulin respectively. ROC analyses with β2 microglobulin, and eGFR also revealed similar findings. Conclusion: This study demonstrates that urinary NGAL is a significant predictor of treatment response in multiple myeloma, particularly in advanced disease stages. Elevated urinary NGAL levels are more strongly linked to worsening renal function and disease burden than S. creatinine. With its high sensitivity and specificity, NGAL serves as a reliable biomarker for identifying patients at risk of renal impairment and monitoring treatment response. Bang. Renal J. 2026; 8(1): 16-23